Highly transparent solid-state artificial synapse based on oxide memristor - Singh, Ranveer; Kumar, Mohit; Iqbal, Shahid; Kang, Hyunwoo; Park, Ji Yong; Seo, Hyungtak (Applied Surface Science, 2021)
A synaptic device based on memristive switching that functionally mimics a biological synapse uses an electronic synapse (like a wire) to realize neuromorphic computing. Conventional two-terminal based memristors can be used for high-performing synaptic devices; however, these memristors suffer from several shortcomings (e.g. reproducibility) due to unstable filament formation during the switching process. Here, a solid state electronic synaptic device based on WO3/NiO/FTO heterostructures has been demonstrated. The typical artificial synaptic device behavior was observed from the current–voltage characteristics under consecutive voltage sweeps which revealing clockwise hysteresis. The schematic of the working mechanism of the solid-state electronic synapses revealed that the presence of the NiO layer, working as a carrier selective layer, enhances the trapping of charge carriers and thereby improves the stability and switching uniformity. In addition, from the analysis on the carrier transport mechanisms, the trap-filled assists space-charge-limited-current conduction mechanism is found to be dominant. This work will be an important step forward towards the realization of low-cost and transparent synaptic behavior.
Keywords: Artificial synapse; Biological synapse; Carrier transport mechanisms; Filament formation; Neuromorphic computing; Solid state electronics; Space charge limited currents; Voltage characteristics; All oxides; Artificial synapse; Charge trapping/detrapping; Highly transparent; Solid-state